Comparison of irrigation protocols for the internal decontamination of dental implants—results of in vitro and in vivo studies. Issue 10 (27th August 2021) - Jervøe‐Storm, Pia‐Merete; Hablützel, Alexandra Selina; Bartels, Philipp; Kraus, Dominik; Jepsen, Søren; Enkling, Norbert
Abstract: Objectives: Previous investigations have shown a progressive bacterial colonization of the internal cavities of two‐piece dental implants with possible implications for peri‐implant bone loss. The aim of the study was to compare different irrigation protocols for the internal decontamination of implants in vitro and in vivo. Materials and Methods: In the in vitro part, 80 samples were obtained 24 h after inoculation with an aliquot of subgingival bacteria from 40 implants as follows: before and after either cleaning with a brush and an irrigation solution (irrigation‐brush‐irrigation: test) or repeated irrigation alone (irrigation‐irrigation: control). In the clinical study, 40 samples from twenty partially edentulous patients contributing each with one implant were collected after removal of abutment and suprastructure with sterile paper points immediately before and after decontamination and subsequently analyzed for total bacterial counts (TBC) by real‐time‐PCR. Irrigation solutions were chlorhexidine (0.2% (CHX)), H2 O2 (10%), alcohol (70%, (ALC)), and NaCl (0.9%). Differences in proportional reduction of TBC between the four irrigation solutions were analyzed. Results: Irrigation with H2 O2 showed the highest effect in both parts of the study (relative TBC reduction in vitro: H2 O2 : 87.1%, CHX: 56.9%, ALC: 43.7%, NaCl: 42.7%; in vivo: H2 O2 : 51.4%, ALC: 30.4%, NaCl: 26.3%, CHX: 7.1%). The additional use of a brush showed no beneficial effect ( p  = 0.088). Overall, H2 O2 was superior to all other irrigation solutions with regard to relative TBC reduction. Conclusions: The present results indicate the potential of an irrigation protocol that includes a 10% H2 O2 solution for the internal decontamination of implants. (ClinicalTrials.gov NCT01917305).